Engineering practice of advance gas control for crushed soft coal seams through directional fracturing using a long borehole in the coal seam roof - Bingyi JIA; Shugang LI; Dongdong CHEN; Qun ZHANG (Meitian dizhi yu kantan)
Objective and MethodsThe crushed soft coal seams susceptible to intense coal and gas outbursts exhibit high gas content and pressure. Consequently, during borehole drilling for regional gas pre-drainage in such coal seams, high blowout intensity is prone to cause gas overrun and low drilling efficiency. To accelerate its development, this study analyzed the status and adaptability of existing technologies for regional advance gas drainage and pressure relief, as well as the fracture propagation characteristics of coal seam roofs during indirect fracturing using boreholes near the roofs. Accordingly, this study proposed an advance gas drainage and pressure relief technology for crushed soft coal seams with mudstone roofs, which integrates directional sandblasting perforation and proppant injection-based segmented hydraulic fracturing within the borehole casing. Furthermore, this study optimized the borehole structure based on stratigraphic characteristics. To verify the proposed technology, this study conducted a field engineering experiment at the Luling coal mine, Huaibei mining area, Anhui Province, completing the drilling and casing cementing of a 520-m-deep borehole. The casing cementing was achieved using a 110-m-long surface casing (diameter: 219 mm), a 520-m-long intermediate casing (diameter: 114.3 mm), and cement slurry injection under pressure. The borehole was divided into nine segments for perforation and fracturing, with 78 holes formed through 39 perforations. The hydraulic fracturing was implemented with single-segment fluid injection volumes ranging from 210 m3 to 420 m3, maximum pumping pressures from 17.8 MPa to 28.3 MPa, and injected proppant ratios from 2.5% to 3.3%.Results and ConclusionsAfter 257 days of gas drainage from the borehole subjected to fracturing, the cumulative pure gas production exceeded 8×105 m3, with a regional pre-drainage rate reaching up to 15.5%. The gas volume fractions within ranges of 0‒15 m and 15‒30 m on both sides of the borehole’s horizontal section decreased by 27.05% and 11.36%, respectively. Concurrently, the gas pressure at planar distances of 0 m and 15 m from the borehole decreased from 2.78 MPa to 1.14 MPa and 1.75 MPa, respectively, with decreasing amplitude exceeding 37%. These results suggest significant effects of regional advance gas drainage and pressure relief, substantiating the feasibility and effectiveness of the proposed technology. In the zone undergoing advance gas drainage and pressure relief, the blowout rate and intensity of boreholes for gas pre-drainage decreased by 57.89% and 67.11%, respectively. Furthermore, the one-time hole-forming rate and hole-supplementing rate of these boreholes increased by 19% and decreased by 74.87%, respectively, with the average shift meterage per of drilling rigs within the same time interval increasing by 34%. No gas anomalies occurred during the borehole drilling, suggesting significant safety benefits. The proposed technology can serve as a reference for the advance control of gas disasters in mines with similar geologic conditions and has been applied to the Huainan mining area.